Faktor yang Mempengaruhi Partisipasi Suami dalam Penggunaan Metode Kontrasepsi di Puskesmas Polebungin Kec. Bontomanai Kab Kepulauan Selayar Sulawesi Selatan Tahun 2024 - Andi Nurfitriana; Dahlia Manurung; Mediana Sembiring (Lembaga Pengembangan Kinerja Dosen, 2024)
The development of men's participation in family planning, especially in the use of contraception, over the last 12 years in Indonesia has not shown a significant increase. Meanwhile, based on data from the 2019 BKKBN, it is stated that men's participation in family planning programs is much lower. The aim of this study was to determine the factors that influence men's participation in using the vasectomy contraceptive method. The type of research used in this research is quantitative research with a cross sectional study design. Based on the research results, it shows that the majority of the sample tribe supports the use of vasectomy contraception, namely 31 people (63.3%) and the minority of the sample does not support the use of vasectomy contraception, namely 18 people (36.7%). Bivariate analysis found that there was no relationship between ethnicity and participation in the use of the vasectomy contraceptive method in the Polebungin District Health Center Area. Bontomanai District. Selayar Islands, South Sulawesi in 2024